Ultrabroadband Polarization-Insensitive Coupler Based on Dual-Core Photonic Crystal Fiber - Tongtong Zhao; Shuqin Lou; Xin Wang; Min Zhou; Zhenggang Lian (IEEE Photonics Journal, 2017)
We propose a dual-core photonic crystal fiber (PCF) for a broad bandwidth polarization-insensitive coupler. To achieve ultrabroadband and polarization-insensitive characteristics, two elliptical fluorine-doped cores are introduced. By optimizing structure parameters and fiber length, a polarization-insensitive 50:50 coupler is achieved. Its coupling ratio stabilizes at 50 ± 1% the in whole optical communication band from 1.255 to 1.725 μm, and the coupling ratio difference between two polarizations is lower than 0.2%. This coupler also has high compatibility with standard single-mode fibers (SMFs) due to low splice loss. Fabrication feasibility is improved due to the use of uniform circular air holes. Tolerance analysis results indicate that the designed coupler has great potential for practical fabrication. High fabrication feasibility and good performance give it great potential to be used in optical communication systems.